Wearable Biodevices Based on Two-Dimensional Materials: From Flexible Sensors to Smart Integrated Systems - Yingzhi Sun; Weiyi He; Can Jiang; Jing Li; Jianli Liu; Mingjie Liu (Nano-Micro Letters)
Highlights Two-dimensional (2D) materials are highlighted for their exceptional mechanical, electrical, optical, and chemical properties, making them ideal for fabricating high-performance wearable biodevices. The review categorizes cutting-edge wearable biodevices by their interactions with physical, electrophysiological, and biochemical signals, showcasing how 2D materials enhance these devices' functionality, mainly including self-powering and human-machine interaction. 2D materials enable multifunctional, high-performance biodevices, integrating self-powered systems, treatment platforms, and human-machine interactions, though challenges remain in practical applications.